A Rare Case of Cardiac Hydatid Disease without Liver and Lungs Involvement - Mohammad Reza Khalilian; Ali Reza Norouzi; Hassan Zamani; Seyed Khalil Forouzan Nia; Somayyeh Noei Teymoordash (Tehran University of Medical Sciences, 2021)
Hydatid disease is a parasitic infection caused by Echinococcus granulosus. Cardiac involvement is rare especially without liver and lungs tissue involvement. We describe a 12-year-old male patient referred to Mofid Children's Hospital, Tehran, Iran in Jul 2020 due to chronic pericardial effusion and suspected tuberculosis infection from Afghanistan. Echocardiography revealed a cystic lesion in the interventricular septum. Thoracic and abdominal computed tomography showed no similar cystic lesion in the lungs and liver. The patient underwent open-heart surgery for cystectomy and medical treatment with albendazole. Histological examination confirmed hydatid cyst diagnosis. The patient was discharged in good condition and oral albendazole was continued.